Electrolyte Disturbances in Patients with Dengue Fever - Muhammad Sarfraz , Arshad Rabbani , Muhammad Shehzad Manzoor , Hira Zahid, Muhammad Sarfraz , Arshad Rabbani , Muhammad Shehzad Manzoor , Hira Zahid (Journal of Rawalpindi Medical College, 2018)
Background: To determine the electrolyte disturbances in patients with dengue fever and dengue hemorrhagic fever. Methods: In this cross-sectional study 110 patients, with dengue fever, were included. Serum electrolytes levels were measured at the fifth and sixth day of fever irrespective of the stage of dengue infection (DF/DHF). Dengue was confirmed by NS1 or IgM/IgG positivity. DHF was labeled as per WHO criteria of Dengue Hemorrhagic fever. Dengue fever was confirmed in 110 patients by NS1 antigen and IgM/IgG positivity by ELISA. Serum sodium, potassium, and chloride concentrations were measured by standard protocols. Results: Average age of patients was 34.02 years with the majority of males (63.6%). Seventy (63.6%) patients were diagnosed as a case of dengue fever (DF) and 40 (34.4%) patients were diagnosed as case of dengue hemorrhagic fever (DHF). Out of the total, 82 (74.5%) patients had NS1 positive, 54 (49.1%) patients had IgG positive and 33 (30%) patients had IgM positive. Although serum electrolytes were higher among patients with DHF as compared to DF but the association was insignificant. Conclusion: Hyponatremia was the most common disturbance in patients with Dengue fever as well as in patients with dengue hemorrhagic fever. No significant association was found in electrolyte disturbances between patients of dengue fever and dengue hemorrhagic fever.